Negative electrode active material for secondary battery, and secondary battery

By coating Si-based active materials with carbon materials of specific D/G ratios, the negative electrode active material maintains structural integrity and conductivity, enhancing battery cycle characteristics and capacity retention.

JP7602459B2Active Publication Date: 2024-12-18PANASONIC ENERGY CO LTD
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
JP2021527673
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2019-06-28
Filing Date
2020-06-24
Publication Date
2024-12-18
Estimated Expiration
2040-06-24

AI Technical Summary

Technical Problem

Si-based active materials for negative electrodes in secondary batteries experience significant volume changes during charging and discharging, leading to weakened particle contacts and reduced electronic conductivity, which deteriorates battery cycle characteristics.

Method used

A negative electrode active material is developed with Si particles dispersed in a silicon oxide or silicate phase, coated with two types of carbon materials having specific D/G ratios in their Raman spectra, where the first carbon material enhances conductivity and acts as a binder for the second carbon material, maintaining a stable conductive path.

Benefits of technology

The proposed active material improves cycle characteristics by stabilizing the negative electrode structure and maintaining conductivity, resulting in higher capacity and better performance over multiple charging cycles.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007602459000002
    Figure 0007602459000002
  • Figure 0007602459000003
    Figure 0007602459000003
  • Figure 0007602459000001
    Figure 0007602459000001
Patent Text Reader

Abstract

The purpose of the present disclosure is to improve the cycle characteristics of a secondary battery that uses an Si-based active material containing Si. A negative electrode active material (Si-based active material) for secondary batteries according to one embodiment of the present invention comprises core particles, each of which is obtained by dispersing Si particles in a silicon oxide phase or a silicate phase, and a carbon material that adheres to the surfaces of the core particles. If a D / G ratio is the ratio of the peak intensity of the D-band to the peak intensity of the G-band in the Raman spectrum, the carbon material contains a first carbon material that has a D / G ratio of from 0.8 to 2 and a second carbon material that has a D / G ratio of from 0.01 to 0.5. The D / G ratio of the carbon material is from 0.2 to 0.9.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present disclosure relates to a negative electrode active material for a secondary battery, and a secondary battery using the active material. [Background technology]

[0002] It is known that Si-based active materials containing Si can absorb more lithium ions per unit volume than carbon-based active materials such as graphite. Therefore, by using Si-based active materials as negative electrode active materials, it is possible to increase the capacity of the battery. On the other hand, since the volume change of Si-based active materials is large when they are charged and discharged, the structure of the negative electrode mixture layer collapses when the charge and discharge are repeated, weakening the contact between the active material particles and making it easy for the electronic conductivity between the active material particles to decrease. This leads to a decrease in the negative electrode capacity.

[0003] In view of this situation, it has been proposed to form a conductive layer such as a carbon coating on the particle surface of a Si-based active material to increase the electronic conductivity of the particle surface. For example, Patent Document 1 discloses an anode active material consisting of a particle core of a metal such as Si capable of forming a lithium alloy and a carbon layer covering the surface of the particle core. Patent Document 2 discloses an anode active material in which metal particles such as Si are embedded in multiple phases of carbon. [Prior art documents] [Patent documents]

[0004] [Patent Document 1] JP 2000-215887 A [Patent Document 2] JP 2000-272911 A Summary of the Invention [Problem to be solved by the invention]

[0005] However, there is still room for improvement in the cycle characteristics of batteries in the conventional techniques including those in Patent Documents 1 and 2. An object of the present disclosure is to improve the cycle characteristics of high-capacity secondary batteries using Si-based active materials. [Means for solving the problem]

[0006] The negative electrode active material for a secondary battery according to the present disclosure is a negative electrode active material for a secondary battery comprising: a core particle having Si particles dispersed in a silicon oxide phase or a silicate phase; and a carbon material attached to a surface of the core particle, wherein the carbon material comprises a first carbon material having a D / G ratio of 0.8 to 2 and a second carbon material having a D / G ratio of 0.01 to 0.5, and the D / G ratio of the carbon material is 0.2 to 0.9, where D / G ratio is the ratio of the peak intensity of the D band to the peak intensity of the G band in a Raman spectrum.

[0007] The secondary battery according to the present disclosure includes a positive electrode, a negative electrode containing the above-described negative electrode active material, and an electrolyte. Effect of the Invention

[0008] The negative electrode active material according to the present disclosure can improve the cycle characteristics of a secondary battery. A secondary battery using the negative electrode active material according to the present disclosure has, for example, a high capacity and excellent cycle characteristics. [Brief description of the drawings]

[0009] [Figure 1] FIG. 1 is a cross-sectional view of a nonaqueous electrolyte secondary battery according to an embodiment. [Diagram 2] FIG. 2 is a cross-sectional view of a negative electrode active material according to an embodiment. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0010] As described above, the Si-based active material containing Si can absorb more lithium ions per unit volume than the carbon-based active material, which contributes to the high capacity of the battery, but the volume change caused by charging and discharging is large, so there is a problem that the use of the Si-based active material reduces the cycle characteristics of the battery. As a result of intensive research to solve this problem, the present inventors have found that the cycle characteristics are specifically improved by using a negative electrode active material in which two types of carbon materials are attached to the surface of a core particle containing Si, and the D / G ratio of the Raman scattering peak (the ratio of the peak intensity of the D band to the peak intensity of the G band in the Raman spectrum) is adjusted to 0.2 to 0.9.

[0011] Generally, a first carbon material having a D / G ratio of 0.8 to 2 in a Raman spectrum contains a lot of diamond structures. On the other hand, a second carbon material having a D / G ratio of 0.01 to 0.5 in a Raman spectrum contains a lot of graphite structures and has excellent electronic conductivity (electrical conductivity). It is considered that the first carbon material improves the electrical conductivity of the core particle surface and also functions as a binder that attaches the second carbon material to the surface of the core particle.

[0012] The negative electrode active material according to the present disclosure, in which the above two types of carbon materials are attached to the surface of the Si-containing core particle, has higher electrical conductivity and smaller volume change during charging and discharging than conventional Si-based active materials. Therefore, it is believed that the use of the negative electrode active material according to the present disclosure suppresses structural destruction of the negative electrode mixture layer and maintains the conductive path between the particles of the negative electrode active material, thereby improving cycle characteristics.

[0013] An example of an embodiment of a secondary battery according to the present disclosure will be described in detail below. A cylindrical battery in which a wound electrode body 14 is housed in a cylindrical exterior can 16 with a bottom is exemplified below, but the exterior can is not limited to a cylindrical exterior can, and may be, for example, a rectangular exterior can, or an exterior made of a laminate sheet including a metal layer and a resin layer. The electrode body may be a wound electrode body formed into a flat shape, or may be a laminated electrode body in which multiple positive electrodes and multiple negative electrodes are alternately laminated with separators between them.

[0014] FIG. 1 is a cross-sectional view of a secondary battery 10 according to an embodiment. As illustrated in FIG. 1, the secondary battery 10 includes a wound electrode assembly 14, an electrolyte, and an outer can 16 that accommodates the electrode assembly 14 and the electrolyte. The electrode assembly 14 has a positive electrode 11, a negative electrode 12, and a separator 13, and has a wound structure in which the positive electrode 11 and the negative electrode 12 are wound in a spiral shape with the separator 13 interposed therebetween. The outer can 16 is a cylindrical metal container with a bottom that is open on one axial side, and the opening of the outer can 16 is closed by a sealing body 17. In the following description, for convenience of explanation, the sealing body 17 side of the secondary battery 10 is referred to as the top, and the bottom side of the outer can 16 is referred to as the bottom.

[0015] The electrolyte is, for example, a non-aqueous electrolyte containing a non-aqueous solvent and an electrolyte salt dissolved in the non-aqueous solvent. The non-aqueous solvent may be, for example, esters, ethers, nitriles, amides, or a mixed solvent of two or more of these. The non-aqueous solvent may contain a halogen-substituted compound such as fluoroethylene carbonate in which at least a part of the hydrogen of the solvent is substituted with a halogen atom such as fluorine. The electrolyte salt may be, for example, a lithium salt such as LiPF6. The non-aqueous electrolyte may contain 1 to 5 mass % of vinylene carbonate (VC). The electrolyte is not limited to a liquid non-aqueous electrolyte, and may be a solid electrolyte or an aqueous electrolyte.

[0016] The positive electrode 11, negative electrode 12, and separator 13 constituting the electrode body 14 are all long strip-shaped bodies, and are alternately stacked in the radial direction of the electrode body 14 by being wound in a spiral shape. The electrode body 14 also has a positive electrode lead 20 connected to the positive electrode 11 by welding or the like, and a negative electrode lead 21 connected to the negative electrode 12 by welding or the like. The negative electrode 12 is formed to have a size slightly larger than the positive electrode 11 in order to prevent lithium precipitation. The two separators 13 are formed to have a size at least slightly larger than the positive electrode 11, and are arranged to sandwich the positive electrode 11, for example.

[0017] Insulating plates 18 and 19 are disposed above and below the electrode body 14, respectively. In the example shown in Fig. 1, a positive electrode lead 20 connected to the positive electrode 11 passes through a through hole in the insulating plate 18 and extends toward the sealing body 17, and a negative electrode lead 21 connected to the negative electrode 12 passes outside the insulating plate 19 and extends toward the bottom side of the outer can 16. The positive electrode lead 20 is connected to the lower surface of an internal terminal plate 23 of the sealing body 17 by welding or the like, and a cap 27, which is a top plate of the sealing body 17 and is electrically connected to the internal terminal plate 23, serves as a positive electrode terminal. The negative electrode lead 21 is connected to the inner bottom inner surface of the outer can 16 by welding or the like, and the outer can 16 serves as a negative electrode terminal.

[0018] A gasket 28 is provided between the exterior can 16 and the sealing body 17 to ensure airtightness inside the battery. The exterior can 16 has a grooved portion 22 formed therein, with part of the side surface protruding inward, to support the sealing body 17. The grooved portion 22 is preferably formed in an annular shape along the circumferential direction of the exterior can 16, and supports the sealing body 17 on its upper surface. The sealing body 17 is fixed to the top of the exterior can 16 by the grooved portion 22 and the open end of the exterior can 16 which is crimped against the sealing body 17.

[0019] The sealing body 17 has a structure in which an internal terminal plate 23, a lower valve body 24, an insulating member 25, an upper valve body 26, and a cap 27 are laminated in this order from the electrode body 14 side. Each member constituting the sealing body 17 has, for example, a disk shape or a ring shape, and each member except the insulating member 25 is electrically connected to each other. The lower valve body 24 and the upper valve body 26 are connected at their respective centers, and the insulating member 25 is interposed between their respective peripheral edges. When the internal pressure of the battery increases due to abnormal heat generation, the lower valve body 24 deforms and breaks so as to push the upper valve body 26 toward the cap 27, thereby cutting off the current path between the lower valve body 24 and the upper valve body 26. When the internal pressure further increases, the upper valve body 26 breaks, and gas is discharged from the opening of the cap 27.

[0020] The positive electrode 11, the negative electrode 12, and the separator 13 that constitute the electrode assembly 14, and in particular the negative electrode active material (Si-based active material 30) contained in the negative electrode 12, will be described in detail below.

[0021] [Positive electrode] The positive electrode 11 has a positive electrode core and a positive electrode mixture layer provided on the surface of the positive electrode core. For the positive electrode core, a foil of a metal such as aluminum or an aluminum alloy that is stable in the potential range of the positive electrode 11, or a film having the metal disposed on the surface layer, can be used. The positive electrode mixture layer contains a positive electrode active material, a conductive agent, and a binder, and is preferably provided on both sides of the positive electrode core except for the core exposed portion to which the positive electrode lead 20 is connected. The positive electrode 11 can be produced, for example, by applying a positive electrode mixture slurry containing a positive electrode active material, a conductive agent, and a binder to the surface of the positive electrode core, drying the coating, and then compressing it to form a positive electrode mixture layer on both sides of the positive electrode core.

[0022] The positive electrode active material is mainly composed of a lithium-containing transition metal composite oxide. Metal elements contained in the lithium-containing transition metal composite oxide include Ni, Co, Mn, Al, B, Mg, Ti, V, Cr, Fe, Cu, Zn, Ga, Sr, Zr, Nb, In, Sn, Ta, and W. An example of a suitable lithium-containing transition metal composite oxide is a composite oxide containing at least one of Ni, Co, and Mn. Specific examples include a composite oxide containing Ni, Co, and Mn, and a composite oxide containing Ni, Co, and Al.

[0023] Examples of the conductive agent contained in the positive electrode mixture layer include carbon materials such as carbon black, acetylene black, ketjen black, and graphite. Examples of the binder contained in the positive electrode mixture layer include fluororesins such as polytetrafluoroethylene (PTFE) and polyvinylidene fluoride (PVdF), polyacrylonitrile (PAN), polyimide resins, acrylic resins, and polyolefin resins. These resins may be used in combination with cellulose derivatives such as carboxymethylcellulose (CMC) or its salts, and polyethylene oxide.

[0024] [Negative electrode] The negative electrode 12 has a negative electrode core and a negative electrode mixture layer provided on the surface of the negative electrode core. For the negative electrode core, a foil of a metal such as copper or a copper alloy that is stable in the potential range of the negative electrode 12, or a film having the metal disposed on the surface layer, can be used. The negative electrode mixture layer contains a negative electrode active material and a binder, and is preferably provided on both sides of the negative electrode core except for the core exposed portion to which the negative electrode lead 21 is connected. The negative electrode 12 can be produced, for example, by applying a negative electrode mixture slurry containing a negative electrode active material and a binder to the surface of the negative electrode core, drying the coating, and then compressing it to form a negative electrode mixture layer on both sides of the negative electrode core.

[0025] The binder contained in the negative electrode mixture layer may be a fluorine-containing resin such as PTFE or PVdF, PAN, polyimide, acrylic resin, polyolefin, or the like, as in the case of the positive electrode 11, but is preferably a rubber-based binder such as styrene-butadiene rubber (SBR). The negative electrode mixture layer may also contain CMC or a salt thereof, polyacrylic acid (PAA) or a salt thereof, PVA, or the like. CMC or a salt thereof functions as a thickener that adjusts the viscosity of the negative electrode mixture slurry to an appropriate range, and also functions as a binder like SBR.

[0026] The negative electrode mixture layer contains a Si-based active material containing Si as a negative electrode active material. As the negative electrode active material, only the Si-based active material may be used, or a carbon-based active material may be used in combination. When a carbon-based active material is used in combination, the compounding ratio of the Si-based active material to the carbon-based active material in the negative electrode mixture layer is preferably 1:99 to 30:70, more preferably 2:98 to 10:90, in mass ratio. If the compounding ratio is within this range, it becomes easy to achieve a high capacity while maintaining good cycle characteristics.

[0027] Suitable carbonaceous active materials include graphite such as flaky graphite, massive graphite, and amorphous graphite, artificial graphite such as massive artificial graphite (MAG), and mesophase carbon microbeads (MCMB). The volume-based median diameter of the graphite particles (hereinafter referred to as "D50") is, for example, 5 μm to 30 μm, preferably 18 μm to 24 μm. D50 is the particle diameter at which the volume integration value becomes 50% in the particle size distribution measured by the laser diffraction scattering method, and is also called the 50% particle diameter or the median diameter.

[0028] FIG. 2 is a cross-sectional view schematically showing an Si-based active material 30 according to an example of an embodiment. As illustrated in FIG. 2, the Si-based active material 30 includes core particles 31 and a carbon material attached to the surface of the core particles 31, and the carbon material includes two types of carbon materials (the first carbon material 32 and the second carbon material 33). The core particles 31 are particles in which Si particles are dispersed in a silicon oxide phase or a silicate phase. As the silicate, lithium silicate is suitable. The core particles 31 are, for example, particles having a D50 smaller than the D50 of the graphite particles. The D50 of the core particles 31 is preferably 1 μm to 20 μm, more preferably 4 μm to 15 μm.

[0029] The core particles 31 have, for example, a sea-island structure in which fine Si particles are substantially uniformly dispersed in an amorphous silicon oxide matrix, and are represented by the general formula SiO x (0.5 ≦ x ≦ 1.6). Alternatively, the core particles 31 have a sea-island structure in which fine Si particles are substantially uniformly dispersed in a lithium silicate matrix represented by the general formula Li 2z SiO (2+z) (0 < z < 2). The lithium silicate phase preferably contains Li2SiO3 (Z = 1) or Li2Si2O5 (Z = 1 / 2) as a main component from the viewpoints of stability, ease of production, lithium ion conductivity, etc. The silicon oxide phase and the silicate phase are composed of, for example, an aggregate of particles finer than the Si particles.

[0030] The content of the Si particles dispersed in the silicon oxide phase or silicate phase is preferably 35 to 75 mass% relative to the mass of the core particles 31 from the viewpoint of achieving both battery capacity and cycle characteristics. For example, if the content of the Si particles is too low, the charge / discharge capacity decreases, and if the content of the Si particles is too high, some of the exposed Si particles that are not covered by the matrix phase come into contact with the electrolyte, resulting in a decrease in cycle characteristics. The average particle size of the Si particles is generally 500 nm or less before charge / discharge, preferably 200 nm or less, and more preferably 50 nm or less. After charge / discharge, the average particle size is preferably 400 nm or less, and more preferably 100 nm or less.

[0031] As described above, the carbon material including the first carbon material 32 and the second carbon material 33 is attached to the surface of the core particle 31. The first carbon material 32 and the second carbon material 33 are carbon materials having different physical properties, and the D / G ratios of the Raman spectra of the first carbon material 32 and the second carbon material 33 are 0.8 to 2 and 0.01 to 0.5, respectively. The D / G ratios of the Raman spectra of the carbon materials attached to the surface of the core particle 31 are 0.2 to 0.9. The Si-based active material 30 having the carbon material with the D / G ratio adjusted within the range attached to the surface thereof maintains the conductive path in the negative electrode mixture layer well and has the function of improving the cycle characteristics of the battery. The Si-based active material 30 may contain three or more types of carbon materials within a range that does not impair the purpose of the present disclosure.

[0032] The Raman spectra of the first carbon material 32 and the second carbon material 33 include a peak at 1330 cm -1 The D-band peak due to the diamond structure is located near 1580 cm -1 The G-band peaks due to the graphite structure appear near the D / G ratio, which is the intensity ratio of the corresponding peaks (I 1330 / I 1580 ) and can be used as an index showing the ratio of diamond structure to graphite structure contained in a carbon material; a higher ratio means a higher amount of diamond structure.

[0033] Since Raman scattering occurs on the surface of a material, the D / G ratio of the Si-based active material 30 is an index showing the ratio of diamond structure to graphite structure on the surface of the active material particle. The D / G ratio of the Si-based active material 30 mainly depends on the amount of the first carbon material 32 and the second carbon material 33 present on the surface of the active material particle, and the D / G ratio of each of the carbon materials. For example, the higher the compounding ratio of the second carbon material 33, the lower the D / G ratio of the Si-based active material 30 tends to be.

[0034] The first carbon material 32 has a D / G ratio of 0.8 to 2, preferably 0.9 to 1.4 in a Raman spectrum, and contains more diamond structures than the second carbon material 33. The second carbon material 33 has a D / G ratio of 0.01 to 0.5, preferably 0.02 to 0.48 in a Raman spectrum, contains more graphite structures than the second carbon material 33, and has high electrical conductivity. In particular, the second carbon material 33 is a material that absorbs and releases lithium ions, and functions as a negative electrode active material.

[0035] The first carbon material 32 adheres to the surface of the core particle 31 more easily than the second carbon material 33, and improves the electrical conductivity of the Si-based active material 30, while also functioning as a binder for the second carbon material 33. The presence of the first carbon material 32 on the surface of the core particle 31 makes it easier for the second carbon material 33 to adhere to the surface of the core particle 31, and the electrical conductivity of the Si-based active material 30 can be effectively improved.

[0036] The first carbon material 32 is present in an amount of preferably 5 to 20 mass %, more preferably 5 to 15 mass %, based on the mass of the Si-based active material 30. The second carbon material 33 is present in an amount of preferably 5 to 70 mass %, more preferably 10 to 70 mass %, based on the mass of the Si-based active material 30. The content of the second carbon material 33 may be equal to or less than the content of the first carbon material 32, but is preferably greater than the content of the first carbon material 32.

[0037] The D / G ratio of the Raman spectrum of the carbon material attached to the surface of the core particle 31 of the Si-based active material 30 is 0.2 to 0.9, and preferably 0.2 to 0.6. The D / G ratio of the Si-based active material 30 can be changed by adjusting the compounding ratio of two kinds of carbon materials as described above. In the Si-based active material 30, the mass ratio of the core particle 31, the first carbon material 32, and the second carbon material 33 is, for example, first carbon material 32<second carbon material 33<core particle 31, or first carbon material 32<core particle 31<second carbon material 33. The core particle 31 is preferably present in an amount of 10 to 85 mass % relative to the mass of the Si-based active material 30, and more preferably 20 to 70 mass %.

[0038] 2, the first carbon material 32 is present in a layered form on the surface of the core particle 31. On the other hand, the second carbon material 33 is in a particulate form. For example, the first carbon material 32 is formed over a wide area on the surface of the core particle 31, and the second carbon material 33 is scattered on the surface of the core particle 31. Both the first carbon material 32 and the second carbon material 33 are present on the particle surface of the Si-based active material 30.

[0039] The shape of the second carbon material 33 may be any of granular (spherical), lump, needle, and fibrous. Examples of the second carbon material 33 include natural graphite, artificial graphite, graphene, carbon fiber, carbon nanotubes (CNTs), highly oriented pyrolytic graphite (HOPG), and mixtures thereof.

[0040] The Si-based active material 30 can be produced, for example, by mixing a core particle 31, a first carbon material 32, and a second carbon material 33 to attach the two types of carbon materials to the surface of the core particle 31, and then heat-treating the mixture. For the first carbon material 32, pitches (petroleum pitch, coal pitch), phenol resin, or other carbonizable resins are used. The first carbon material 32 may be formed on the surface of the core particle 31 by a CVD method using acetylene, methane, or the like. For the second carbon material 33, a carbon-based active material such as graphite may be used.

[0041] For mixing the core particles 31 and the carbon material, a conventionally known mixer can be used, examples of which include a container rotation type mixer such as a planetary ball mill, an air flow agitator, a screw type blender, a kneader, etc. The heat treatment is carried out, for example, in an inert atmosphere at a temperature of 700°C to 900°C for several hours.

[0042] [Separator] A porous sheet having ion permeability and insulating properties is used for the separator 13. Specific examples of the porous sheet include a microporous thin film, a woven fabric, and a nonwoven fabric. The material of the separator 13 is preferably an olefin resin such as polyethylene or polypropylene, or cellulose. The separator 13 may have either a single-layer structure or a laminated structure. A heat-resistant layer or the like may be formed on the surface of the separator 13. EXAMPLES

[0043] The present disclosure will be further described below with reference to examples, but the present disclosure is not limited to these examples.

[0044] <Comparative Example 1> [Preparation of Si-based active material] The Si-containing particles (core particles) and the first carbon material were mixed in a mass ratio of 98:2 using a planetary ball mill (Fritsche, P-7 type) at 100 rpm for 1 hour, and a composite treatment was performed to attach the first carbon material to the surface of the Si-containing particles. The composite particles were heat-treated in an inert atmosphere at 800°C for 5 hours to obtain a Si-based active material.

[0045] The Si-containing particles used were particles with a D50 of 10 μm, in which fine particles of Si were dispersed in a lithium silicate phase. The first carbon material used was petroleum pitch with a D / G ratio of 0.9 in the Raman spectrum. The D / G ratio of the Raman spectrum of the carbon material attached to the core particles was 0.9. The D / G ratios of the carbon material attached to the core particles and the first carbon material are shown in Table 1 (the same applies to the following Comparative Examples and Examples). The Raman spectrum was measured using an NRS-5100 manufactured by JASCO Corporation. The D / G value of the Raman spectrum of the carbon material alone was determined by heat-treating only the carbon material at 800° C. and performing Raman measurement.

[0046] [Preparation of negative electrode] The negative electrode active material was a mixture of the above-mentioned Si-based active material and natural graphite with a D50 of 22 μm in a mass ratio of 5:95. The negative electrode active material, carboxymethyl cellulose (CMC), and styrene-butadiene rubber (SBR) were mixed in a solid content mass ratio of 100:1.5:1.0, and a negative electrode mixture slurry with a solid content concentration of 50 mass% was prepared using water as a dispersion medium. Next, the negative electrode mixture slurry was applied to both sides of a negative electrode core made of copper foil by a doctor blade method, and the coating film was dried and compressed, and then cut into a predetermined electrode size to prepare a negative electrode in which a negative electrode mixture layer was formed on both sides of the negative electrode core.

[0047] [Preparation of electrolyte] Lithium hexafluorophosphate (LiPF6) was dissolved at a concentration of 1.4 mol / L in a solvent in which ethylene carbonate (EC) and methyl ethyl carbonate (MEC) were mixed at a volume ratio of 30:70. Furthermore, vinylene carbonate (VC) was dissolved at a concentration of 2 mass% relative to the total amount of the electrolyte to prepare an electrolyte.

[0048] [Battery construction] The metallic Li and the negative electrode were wound with a separator made of a microporous polyethylene film interposed therebetween, and then molded into a flat shape, and a polypropylene tape was attached to the outermost circumference to prepare a flat wound electrode body. In a glove box under an argon atmosphere, the electrode body and the non-aqueous electrolyte were housed in an exterior body made of a laminate sheet including an aluminum alloy layer, and then the pressure inside the exterior body was reduced to impregnate the separator with the electrolyte, and the opening of the exterior body was sealed to prepare a non-aqueous electrolyte secondary battery.

[0049] <Comparative Example 2> A secondary battery was produced in the same manner as in Comparative Example 1, except that in producing the Si-based active material, 2 mass % of the first carbon material was attached to the surface of the Si-containing particles by chemical vapor deposition (CVD).

[0050] <Comparative Example 3> A secondary battery was produced in the same manner as in Comparative Example 1, except that in the production of the Si-based active material, a second carbon material was used instead of the first carbon material, the Si-containing particles and the second carbon material were mixed in a mass ratio of 90:10, and the second carbon material was attached to the surfaces of the Si-containing particles using a planetary ball mill. Natural graphite with a D50 of 3 μm was used as the second carbon material.

[0051] <Comparative Example 4> A secondary battery was produced in the same manner as in Comparative Example 3, except that a mixture of natural graphite and artificial graphite having a D50 of 22 μm was used as the second carbon material.

[0052] <Comparative Example 5> A secondary battery was produced in the same manner as in Comparative Example 3, except that pyrolytic graphite having a D50 of 30 μm was used as the second carbon material.

[0053] <Comparative Example 6> A secondary battery was produced in the same manner as in Comparative Example 1, except that in producing the Si-based active material, the Si-containing particles, the first carbon material, and the second carbon material were mixed in a mass ratio of 88:10:2. The same material as in Comparative Example 4 (a mixture of natural graphite and artificial graphite) was used as the second carbon material.

[0054] <Example 1> A secondary battery was produced in the same manner as in Comparative Example 1, except that in producing the Si-based active material, the Si-containing particles, the first carbon material, and the second carbon material were mixed in a mass ratio of 85:10:5. The same material (natural graphite) as in Comparative Example 3 was used as the second carbon material.

[0055] <Example 2> A secondary battery was produced in the same manner as in Comparative Example 6, except that in producing the Si-based active material, the Si-containing particles, the first carbon material, and the second carbon material were mixed in a mass ratio of 81:10:9.

[0056] <Example 3> A secondary battery was produced in the same manner as in Comparative Example 6, except that in producing the Si-based active material, the Si-containing particles, the first carbon material, and the second carbon material were mixed in a mass ratio of 85:10:5.

[0057] <Example 4> A secondary battery was produced in the same manner as in Comparative Example 6, except that in producing the Si-based active material, the Si-containing particles, the first carbon material, and the second carbon material were mixed in a mass ratio of 70:10:20.

[0058] <Example 5> A secondary battery was produced in the same manner as in Comparative Example 6, except that in producing the Si-based active material, the Si-containing particles, the first carbon material, and the second carbon material were mixed in a mass ratio of 20:10:70.

[0059] <Example 6> A secondary battery was produced in the same manner as in Comparative Example 1, except that in the production of the Si-based active material, the Si-containing particles, the first carbon material, and the second carbon material were mixed in a mass ratio of 40:10:50. The same material (pyrolytic graphite) as in Comparative Example 5 was used as the second carbon material.

[0060] <Example 7> A secondary battery was produced in the same manner as in Example 6, except that the mass ratio of the Si-containing particles, the first carbon material, and the second carbon material was 20:10:70.

[0061] <Example 8> A secondary battery was produced in the same manner as in Comparative Example 1, except that in producing the Si-based active material, the first carbon material was attached by a CVD method to the surfaces of the Si-containing particles mixed with the second carbon material so that the mass ratio of the Si-containing particles, the first carbon material, and the second carbon material was 70:10:20.

[0062] <Example 9> A secondary battery was produced in the same manner as in Example 6, except that the mass ratio of the Si-containing particles, the first carbon material, and the second carbon material was 85:10:5, and artificial graphite with a D50 of 15 μm was used as the second carbon material.

[0063] [Evaluation of cycle characteristics (measurement of capacity retention)] Each secondary battery of the examples and comparative examples was subjected to CCCV charging (current 0.1 It, end voltage 0.005 V, end current 0.01 It) in a temperature environment of 25°C, and then CV discharging (current 0.1 It, end voltage 1.5 V). This charge / discharge cycle was counted as one cycle, and 10 cycles were performed, and the capacity retention rate of each battery was calculated by the following formula. The evaluation results are shown in Table 1 together with the D / G ratio of the Raman spectrum of the Si-based active material. Capacity retention rate = (10th cycle discharge capacity / 1st cycle discharge capacity) x 100

[0064] [Table 1]

[0065] As shown in Table 1, all of the batteries of the examples have higher capacity retention rates and better cycle characteristics than the batteries of the comparative examples. That is, by using two types of carbon materials with Raman spectrum D / G ratios of 0.8 to 2 and 0.01 to 0.5, respectively, and using a Si-based active material with an adjusted D / G ratio of 0.2 to 0.9, the cycle characteristics of the battery are significantly improved. When either the first carbon material or the second carbon material is not present on the surface of the core particle, or when the above D / G ratio condition is not satisfied, the negative electrode capacity decreases significantly during charging and discharging. [Explanation of symbols]

[0066] REFERENCE SIGNS LIST 10 secondary battery, 11 positive electrode, 12 negative electrode, 13 separator, 14 electrode body, 16 outer can, 17 sealing body, 18, 19 insulating plate, 20 positive electrode lead, 21 negative electrode lead, 22 grooved portion, 23 internal terminal plate, 24 lower valve body, 25 insulating member, 26 upper valve body, 27 cap, 28 gasket, 30 Si-based active material, 31 core particle, 32 first carbon material, 33 second carbon material

Claims

1. A core particle having Si particles dispersed in a silicon oxide phase or a silicate phase; a carbon material attached to a surface of the core particle; A negative electrode active material for a secondary battery comprising: When the ratio of the peak intensity of the D band to the peak intensity of the G band in the Raman spectrum is defined as the D / G ratio, the carbon material comprises a first carbon material having a D / G ratio of 0.8 to 2 and a second carbon material having a D / G ratio of 0.01 to 0.5; The carbon material has a D / G ratio of 0.2 to 0.9; the first carbon material is present in an amount of 5 to 20% by mass relative to the mass of the secondary battery negative electrode active material; The second carbon material is present in an amount of 5 to 70% by mass based on the mass of the negative electrode active material for secondary batteries.

2. The negative electrode active material for secondary batteries according to claim 1 , wherein the first carbon material is present in the form of a layer on the surface of the core particle.

3. The negative electrode active material for a secondary battery according to claim 1 , wherein the second carbon material is in a particulate form.

4. A negative electrode comprising the negative electrode active material according to any one of claims 1 to 3; A positive electrode and An electrolyte; A secondary battery comprising:

Citation Information

Patent Citations

  • Negative electrode material for lithium secondary battery, lithium secondary battery and charging method for lithium secondary battery

    JP2000215887A

  • Metal-carbon composite particle, its production, cathode material, cathode for lithium secondary battery and lithium secondary battery

    JP2000272911A

  • Anode active material for lithium secondary batteries, method for manufacturing the same, and lithium secondary battery containing the same

    JP2012523674A

  • Negative electrode material for lithium ion secondary batteries, negative electrode for lithium ion secondary batteries, and lithium ion secondary battery

    JP2015210962A

  • Separator for nonaqueous electrolyte secondary battery, and nonaqueous electrolyte secondary battery

    JP2018032649A